Focused Analysis: YouTube's Role in Understanding Difficult Concepts & Exam Preparation - Choudhary, Satyanarayan; Kandel, Laxman; Khatri, Bishnu Bahadur (NPRC Journal of Multidisciplinary Research, 2025)
Background: The proliferation of digital learning platforms has positioned YouTube as a dominant resource in student learning ecosystems, particularly for exam preparation and conceptual understanding. While studies acknowledge its widespread use, questions persist regarding its actual educational efficacy and relationship to academic performance. Objective: This study examines the predictive relationship between YouTube usage frequency for exam preparation and students' perceived academic improvement, while addressing gaps in existing literature regarding platform-specific learning impacts. Methods: A quantitative cross-sectional design was employed, collecting data from 390 university students via a validated survey instrument. Reliability analysis confirmed strong internal consistency (α=0.866). Statistical analyses included Pearson correlation and simple linear regression to assess the relationship between usage frequency and perceived academic benefits. Findings: Results revealed a significant positive relationship (β=0.811, p